(untitled)
For any given symmetric measure µ on the closed unit disk D , we apply the Berezin transform to characterizing semi-commuting and commuting Toeplitz operators with bounded harmonic symbols on A^2 (D , dμ). , number=2, journal=Communications in Mathematical Research, year=2021, month=May, pages=165–176